Analysis of the Determining Factors of Taxpayer's Interest in Using E-Filing - Wahdi, Nirsetyo; Utari, Vika Marselisna; Santoso, Aprih (Indonesian Journal of Islamic Economics and Finance, 2022)
The modernization of the tax administration system includes self-registration as a taxpayer through e-registration, filling out electronic tax returns through e-SPT, making tax payment codes through e-billing, filling out tax invoices through e-Faktur, and electronic tax reporting through e-filing. . This study aims to determine the factors that influence the intention of taxpayers in using e-filing at the Semarang City Pratama Tax Service Office. The sampling technique used was convenience sampling. This study's sample number was 150 individual taxpayers registered at the KPP Pratama Semarang City. It is collecting data using a questionnaire. The method of analysis in this study is multiple linear regression analysis, calculated using SPSS 23. The results of this study indicate that perceived usefulness, perceived convenience, attitudes, subjective norms, behavioral control, and volunteerism do not affect taxpayers' intention to use e-filing. The perception of understanding, security, and confidentiality affect taxpayers' intention to use e-filing. The suggestions are: 1. It is expected to conduct counseling or socialization of taxpayers who have not used e-filing so that taxpayer knowledge about e-filing can increase. 2. It is expected to improve the security and confidentiality of the data of taxpayers who have used e-filing. It is expected to conduct counseling or socialization of taxpayers who have not used e-filing so that taxpayer knowledge about e-filing can increase. 2. It is expected to improve the security and confidentiality of the data of taxpayers who have used e-filing. It is expected to conduct counseling or socialization of taxpayers who have not used e-filing so that taxpayer knowledge about e-filing can increase. 2. It is expected to improve the security and confidentiality of the data of taxpayers who have used e-filing.